Paraoxonase 192 polymorphism and its relationship to serum lipids in Turkish renal transplant recipients - (:unkn) unknown (ELSEVIER SCIENCE INC, 2004)
Background. Cardiovascular disorders are the leading cause of death in patients with chronic renal. insufficiency. Paraoxonase (PON1) gene variants have been identified as risk factors for cardiovascular disease (CVD). Methods. We investigated the effect of PON1 192 polymorphisms on serum lipid profiles in 29 renal transplant recipients and 26 control subjects. Distribution of the PON1 192-gene polymorphism was determined by polymerase chain reaction-based restriction fragment length polymorphism. Serum lipid levels were measured enzymatically. Results. Frequencies of PON1 192 AA, BB, and AB genotypes among the renal transplant recipients were 38.5%, 26.9%, and 34.6%, and among control subjects they were 35.75%, 17.9%, 46.4%, respectively. The genotype distribution for the PON1 192 polymorphism was not different between the two groups (P = NS, chi-square test). The PON1 192 polymorphisms failed to consistently influence the serum lipid profiles in renal transplant recipients. Conclusion. We have shown that the 192 polymorphism of the PON1 gene is not associated with increased cardiovascular risk in renal transplant recipients.
Keywords: LIPOPROTEIN ASSOCIATED PARAOXONASE; LOW-DENSITY-LIPOPROTEIN; CORONARY HEART-DISEASE; ARYLESTERASE; RISK; GENE